2013
DOI: 10.1111/1365-2745.12179
|View full text |Cite
|
Sign up to set email alerts
|

Long‐tongued insects promote disassortative pollen transfer in style‐dimorphic Narcissus papyraceus (Amaryllidaceae)

Abstract: Summary1. In hermaphroditic flowers, reciprocal herkogamy, for example heterostyly, enhances pollen transfer between floral morphs (disassortative pollination) while avoiding self-interference between sexual organs. By contrast, disassortative pollination might be compromised in style-dimorphic flowers, which lack perfect reciprocity between the two floral morphs. This suboptimal functioning has been considered to explain why stylar dimorphism is rare in nature.2. Some style-polymorphic species receive a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 71 publications
6
66
2
2
Order By: Relevance
“…3G ). Elsewhere among heteromorphic plants, high levels of disassortative mating resulting in equal morph ratios have been reported in self-compatible, tristylous Eichhornia paniculata ( Barrett et al, 1987 ;Kohn and Barrett, 1992 ) and in stylar dimorphic Narcissus papyraceus ( Simón-Porcar et al, 2014, 2015a. We observed abundant pollinator visitation by long-tongued bees in distylous Glandora and Lithodora populations ( Ferrero et al, 2011b ) and these insects probably play a key role in promoting disassortative mating and causing isoplethic morph ratios.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…3G ). Elsewhere among heteromorphic plants, high levels of disassortative mating resulting in equal morph ratios have been reported in self-compatible, tristylous Eichhornia paniculata ( Barrett et al, 1987 ;Kohn and Barrett, 1992 ) and in stylar dimorphic Narcissus papyraceus ( Simón-Porcar et al, 2014, 2015a. We observed abundant pollinator visitation by long-tongued bees in distylous Glandora and Lithodora populations ( Ferrero et al, 2011b ) and these insects probably play a key role in promoting disassortative mating and causing isoplethic morph ratios.…”
Section: Discussionsupporting
confidence: 52%
“…For example, in stigma dimorphic Narcissus assoanus , both L-morph biased and isoplethic populations are reported in southern France and these differ in size and the quantity and quality of pollinator service ( Baker et al, 2000a , c ). Diff erences in the types of pollinators visiting populations of other stigma-height dimorphic Narcissus species have also been implicated in causing variation in morph ratios ( Arroyo and Dafni, 1995 ;Simón-Porcar et al, 2014 ). A theoretical model of pollination and mating in stigma-height dimorphic populations, based on empirical data on the fl oral biology of Narcissus species, demonstrated that greater assortative mating in the L-morph, because of the reduced herkogamy of this morph compared to the S-morph, could explain the L-biased populations that are most commonly encountered in this genus ( Baker et al, 2000a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts from long-to short-tongued pollinators seem to select against the S morph and favour the L morph [59,60]. Thus, a steeper fitness surface could be expected in populations where flowers have close fit with pollinators (long-tongued insects) than in populations in which pollinators fit loosely with flowers (short-tongued insects), and this should be reflected in the patterns of phenotypic integration [2,18].…”
Section: Discussion (A) Patterns Of Phenotypic Integration In Narcissmentioning
confidence: 99%
“…Furthermore, differences between population types in the average correlation between anther height and flower tube length were larger for the lower anther level than the upper anther level. This may reflect two processes that are not mutually exclusive: (i) selection generated by LT-pollinators for a precise position of the lower anther level to donate pollen to S-stigmas in dimorphic populations [58,92]; and/or (ii) relaxation of selection on the lower anther level in L-monomorphic populations because, unlike long-tongued insects, short-tongued pollinators interact only with the upper anther level (R Pérez-Barrales 2003, personal observation; [60]). …”
Section: Discussion (A) Patterns Of Phenotypic Integration In Narcissmentioning
confidence: 99%